MAGI2-AS3 hypermethylated in promoter region promotes migration and invasion of head and neck squamous cell carcinoma via miRNA-31-5p/AR axis - Kai Yue; Ting Zhang; Huanhuan Wang; Bo Wang; Yalin Mu; Hui Li (Translational Oncology)
Molecular regulatory mechanism of MAGI2-AS3 in HNSCC is not yet mature.In this study, we analyzed the methylation level of MAGI2-AS3 promoter and its downstream miR-31-5p/AR axis by bioinformatics methods. qRT-PCR was used to detect the mRNA expression level of each gene, and western blot was used to detect the expression level of AR proteins in tissues and cells. CCK-8, colony formation, wound healing, and cellular invasion assays were used to detect the HNSCC cell proliferation, migration, and invasion. Dual luciferase and RIP assays were performed to validate the binding relationship between genes. The effect of MAGI2-AS3 on HNSCC progression was verified in nude mice in vivo.The low expression of MAGI2-AS3 in HNSCC was caused by hypermethylation of MAGI2-AS3, which could regulate the target of miR-31-5p by sponge adsorption of miR-31-5p, and miR-31-5p could inhibit the expression of AR by directly targeting AR. Thus, MAGI2-AS3 could inhibit the proliferation, migration, and invasion of HNSCC through the miR-31-5p/AR axis. This provided a theoretical basis that MAGI2-AS3 was a potential therapeutic target for HNSCC.